1972
DOI: 10.1139/v72-599
|View full text |Cite
|
Sign up to set email alerts
|

The Trifluoroacetic Acid Solvent System. Part IV. Triple Ions

Abstract: Electrolytes studied in 100'j/, trifluoroacetic acid exhibit a minimum in equivalent conductivity with increasing solute concentration. This behavior is accounted for by the formation of triple-ions at higher concentrations. Triple-ion dissociation constants, k , have been evaluated and, in general, they show the opposite trend with changing ion size to that of the ion-pair dissociation constants; that is the triple-ions of smaller ions are more dissociated. The experimentally observed trend is accounted for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1974
1974
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…Values of '11' for potassium permanganate varied from 3.0 at high concentration (0.05 molal) to 5.2 at low concentration (0.004 molal). Interestingly water appeared to behave like an electrolyte at low concentration (n = 1.8 at 0.012 molal), although conductivity studies have shown that it is not an electrolyte (3,30). Similar anomalous behaviour has been observed for water in nitric acid (31).…”
Section: Cryoscopysupporting
confidence: 61%
“…Values of '11' for potassium permanganate varied from 3.0 at high concentration (0.05 molal) to 5.2 at low concentration (0.004 molal). Interestingly water appeared to behave like an electrolyte at low concentration (n = 1.8 at 0.012 molal), although conductivity studies have shown that it is not an electrolyte (3,30). Similar anomalous behaviour has been observed for water in nitric acid (31).…”
Section: Cryoscopysupporting
confidence: 61%